The Impact of Post-Trauma in The Personality Development in Matt Haig's The Midnight Library: A Pshycoanalytical Study of Character - Rozadi, Farhan (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2022)
The Midnight Library represents that childhood trauma is something that happens to a child unconsciously. This study indicates that trauma that occurred in a child's past can affect the development of his character in adulthood. This study examines Matt Haig's novel The Midnight Library, with the close reading method. Psychoanalysis is a research method used in this study. This study looks at how the influence of trauma on the main character in a novel. There seems to influence the decision-making of an adult woman who was traumatized in her youth. The tendency to make decisions from the subconscious affects the woman.